Effects of different disinfection treatments on the natural microbiota of lettuce - Nascimento, M. S.; Silva, N.; Catanozi, MPLM; Silva, K. C. (Int Assoc Food Protection, 2003)
In this study, water and eight sanitizing solutions (vinegar at 6, 25, and 50%; acetic acid at 2 and 4%; peracetic acid at 80 ppm, sodium hypochlorite at 200 ppm, and sodium dichloroisocyanurate at 200 ppm) were compared in terms of their effectiveness against the natural microbiota of lettuce. All of the samples were kept in contact with the sanitizing solutions for 15 min, and the effectiveness of a sanitizing agent was evaluated on the basis of the number of decimal reductions of the total aerobic mesophilic count, the mold and yeast count, the total coliform count, and the Escherichia coli count. The average initial levels of these organisms in the samples were 6.94 log(10) CFU/g for aerobic mesophilic microorganisms, 5.62 log(10) CFU/g for molds and yeasts, and 3.25 log(10) CFU/g for total coliforms. of 10 samples analyzed, only 4 contained E. coli, and the average initial level of this microorganism in these 4 samples was 1.64 log(10) CFU/g. Salmonella was not detected in any of the samples tested. The decimal reductions of the populations of aerobic mesophilic microorganisms, molds and yeasts, total coliforms, and E. coli were 0.78, 0.87, 0.82, and >0.14 log(10) CFU/g, respectively, in water; 2.89, >3.41, >2.21, and >0.26 log(10) CFU/g, respectively, in 50% vinegar; 2.42, >3.20, >1.99, and >0.26 log(10) CFU/g, respectively, in 25% vinegar; 1.83, 2.57, 1.58, and >0.26 log(10) CFU/g, respectively, in 6% vinegar; 3.91, >3.58, >2.25, and >0.26 log(10) CFU/g, respectively, in 4% acetic acid; 3.37, >3.53, >2.25, and >0.26 log(10) CFU/g, respectively, in 2% acetic acid; 1.85, 2,32, 1.44, and >0.20 log(10) CFU/g, respectively, in 80 ppm of peracetic acid; 2.63, 2.75, 1.91, and >0.26 log(10) CFU/g, respectively, in 200 ppm of sodium hypochlorite; and 3.23, >3.08, >1.95, and >0.26 log(10) CFU/g, respectively, in 200 ppm of sodium dichloroisocyanurate. Statistical analysis of the results showed that the effectiveness levels for all of the sanitizing agents tested were equivalent to or higher than that for sodium hypochlorite at 200 ppm.